2022
DOI: 10.1108/sef-09-2021-0371
|View full text |Cite
|
Sign up to set email alerts
|

Investor attention and cryptocurrency price crash risk: a quantile regression approach

Abstract: Purpose Motivated by the lure of cryptocurrencies for retail investors, whose concentrated holdings are particularly exposed to price crash risk, this paper aims to study the relationship between investor attention and crash risk for a range of cryptocurrencies. Design/methodology/approach This study adopts a quantile regression approach to determine the effect of investor attention on crash risk. Crash risk is measured using the negative coefficient of skewness and down up volatility. Findings This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Investors’ attention has been argued to be an important determinant of cryptocurrency pricing. Smales (2021) showed that investors’ attention had a positive relationship with the cryptocurrency price. Similarly, others have highlighted that investors’ attention had the potential to improve prediction accuracy for Bitcoin returns.…”
Section: Resultsmentioning
confidence: 99%
“…Investors’ attention has been argued to be an important determinant of cryptocurrency pricing. Smales (2021) showed that investors’ attention had a positive relationship with the cryptocurrency price. Similarly, others have highlighted that investors’ attention had the potential to improve prediction accuracy for Bitcoin returns.…”
Section: Resultsmentioning
confidence: 99%
“…The application of machine learning techniques, including regression models, SVMs and random forests, has been used to analyze historical data and identify patterns or indicators that can signal price movements of cryptocurrencies (Jaquart et al, 2022;Smales, 2022). Additionally, deep learning methods, particularly recurrent neural networks, convolutional SEF 41,2 neural networks (CNNs) and LSTM networks, have gained popularity because of their ability to capture temporal dependencies in sequential data (Lahmiri and Bekiros, 2019;Alonso-Monsalve et al, 2020;Zhong et al, 2023;Oyedele et al, 2023).…”
Section: Machine Learning and Cryptocurrencymentioning
confidence: 99%